Does aid effectiveness depend on the quality of donors? - Anna Minasyan; Peter Nunnenkamp; Katharina Richert (Kiel Institute for the World Economy (IfW), 2016)
The question of whether aid recipient countries would benefit from stronger income effects if foreign donors provided higher quality aid has received scant attention so far. We make use of the ranking of donors by the Center for Global Development to compare the effects of quality-adjusted aid and unadjusted aid on changes in GDP per capita. Our difference-in-difference-in-differences analysis reveals significant treatment effects for quality-adjusted aid, while we do not find significant treatment effects for unadjusted aid. The quality of aid matters most when accounting for delayed effects. However, our results depend on the sample of recipient countries.
Keywords: F35; 330; donor ranking; quality-adjusted aid; income effects; DDD analysis